Basic & clinical pharmacology - Katzung, Bertram G.; Masters, Susan B.; Trevor, Anthony J. (New York McGraw-Hill Medical London McGraw-Hill [distributor], 2012)
Looks at the essential conepts in the science of pharmacology and its application to clinical practice.
Basic principles -- Autonomic drugs -- Cardiovascular-renal drugs -- Drugs with important actions on smooth muscle -- Drugs that act in the central nervous system -- Drugs used to treat diseases of the blood, inflammation, & gout -- Endocrine drugs -- Chemotherapeutic drugs -- Toxicology -- Special topics.
Previous ed.: 2009.
Includes bibliographical references and index.
Keywords: Pharmacology; Pharmacology, Clinical; Clinical pharmacology; Pharmacology